EVIDENCES OF DEFORMATIONS OF MINERALS OF THE BERKUT QUARTZ VEIN (SOUTH URALS) AFFECTED BY DYNAMOMETAMORPHIC PROCESSES - L.Ya. Kabanova (Минералогия)
The article examines petrography and mineralogy of rocks of the Berkut quartz-feldspar vein in the South Urals, which is characterized by intense deformation in comparison with numerous quartz veins of the Kyshtym block. These data allowed the sequence of formation and transformation of the Berkut vein. The vein is a typical vein of replacement, which is composed of blocks of quartz and granite rocks, and contains relics of host rocks (amphibolites and gneisses). Our studies revealed the tectonic transformations of rocks and minerals, as well as the deformation mechanisms with leading plastic deformation and processes of dissolution of minerals under pressure together with brittle fracturing. Dissolution and further deposition led to the crystallization of minerals of new generations (quartz, albite, and oligoclase) and often minerals of different composition (biotite after amphibole). Subsequent metasomatosis is responsible for new generations of minerals (quartz, albite, microcline, muscovite, epidote, zoisite, and clinozoisite) with different morphology and crystal optical properties.